Missed medical appointments during shifts to and from daylight saving time. (3rd April 2018) - Ellis, David A.; Luther, Kirk; Jenkins, Rob
ABSTRACT: Transitions into and out of Daylight Saving Time (DST) can provide insights into how a minor change to a regular sleep–wake cycle can inadvertently affect health. We examined the relationship between DST and missed medical appointments. Using a large dataset, the proportion of missed appointments were examined prior and post spring and autumn clock changes. As predicted, the number of missed medical appointments significantly increased following the spring (forward) clock change and the week of the clock change. This trend was reversed following the transition out of DST. The implications of scheduling appointments around DST to increase attendance are discussed.